Immediate-Early Genes and Delayed Primary Response Genes Regulated by NmU in SKBR3 HER-2 Positive Breast Cancer Cell Line - Jessica Murphy; Sweta Rani (SURE Journal: (Science Undergraduate Research Experience Journal))
BackgroundBreast cancer is a heterogeneous disease that consists of varying genetic, cellular and molecular subtypes with unique characteristics. Due to the multiple subtypes and molecular markers of breast cancer, successful clinical treatment is hampered by the lack of reliable biomarkers. HER2-positive breast cancer is an aggressive subtype associated with poor patient prognosis. Although survival rates have dramatically increased due to the development of Trastuzumab in 1997, many patients develop a resistance to this therapeutic treatment and relapse over time. Rani et al. (2014), have associated the acquirement of resistance to HER2-treatment with Neuromedin U, but the mechanisms by which it works remain elusive. AimThe aim of this study was to investigate the effects of NmU on the regulation of immediate early and delayed primary response genes in HER2-positive SKBR3 breast cancer cells using RT-qPCR gene expression analysis. This information was then used to uncover related pathways that may be involved in the progression of this aggressive cancer due to NmU. ResultsTreatment of SKBR3 cells with endogenous NmU resulted in a significant change in the regulation of several cancer-associated genes. Jun expression was significantly downregulated after 30 minutes of NmU treatment, which increased significantly after 1 hour. EGR1 and NR4A1 expression levels were also significantly downregulated. EGR1 and NR4A1 act as tumour suppressors in certain human cancers, suggesting that NmU may drive cancer progression by inhibiting important tumour suppressors. Increasing regulation of SOD2 and DKK1 was observed due to NmU, suggesting that NmU plays a role in Wnt and MAPK signalling. ConclusionThis project has identified a number of critical genes that may induced by NmU. Through further research, this could lead to the potential development of alternative therapies for HER2-positive breast cancer by targeting these genes.